2023
DOI: 10.3389/fcimb.2023.1109418
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant gram-negative bacterial infection in intensive care unit patients: Antibiotic resistance analysis and predictive model development

Abstract: In this study, we analyzed the antibiotic resistance of carbapenem-resistant gram-negative bacteria (CR-GNB) in intensive care unit (ICU) patients and developed a predictive model. We retrospectively collected the data of patients with GNB infection admitted to the ICU of the First Affiliated Hospital of Fujian Medical University, who were then divided into a CR and a carbapenem-susceptible (CS) group for CR-GNB infection analysis. Patients admitted between December 1, 2017, and July 31, 2019, were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A previous study [ 35 ] suggested that three or more antibiotic classes were a risk factor for multidrug-resistant A. baumannii infections. This might be attributed to the fact that combination antibiotic treatment causes dysbiosis in the microbiota, whereby the majority of susceptible bacteria are eradicated, while the antibiotic-resistant strains survive [ 36 ]. Additionally, inappropriate combination antibiotic treatment can create selective pressure, thus increasing the likelihood of antibiotic-resistant infection and promoting the selection of drug-resistant bacteria [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 35 ] suggested that three or more antibiotic classes were a risk factor for multidrug-resistant A. baumannii infections. This might be attributed to the fact that combination antibiotic treatment causes dysbiosis in the microbiota, whereby the majority of susceptible bacteria are eradicated, while the antibiotic-resistant strains survive [ 36 ]. Additionally, inappropriate combination antibiotic treatment can create selective pressure, thus increasing the likelihood of antibiotic-resistant infection and promoting the selection of drug-resistant bacteria [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CNSIs are characterized by substantial morbidity, fatality rates, and significant costs imposed on the healthcare system ( 14 ). In recent years, there has been an increasing prevalence of Acinetobacter baumannii and Klebsiella pneumoniae in hospital-acquired infections ( 15 ). Bacterial infections affecting the central nervous system represent a medical emergency, necessitating prompt diagnosis and immediate treatment.…”
Section: Resultsmentioning
confidence: 99%